Hormonal replacement therapy in the treatment of female urinary tract disfunctions – myths and facts - Adamiak, Aneta; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
The epidemiological studies reveal that menopause with subsequent hormonal defficiency plays an important role in the etiology of a number of urogenital complaints. In this period the increased occurrence of stress urinary incontinence, overactive bladder and recurrent tract urinary infection is observed. The aim of this paper is to present the actual knowledge about influence of sex steroids on the female lower urinary tract and substantiate the rationale for the hormone replacement therapy in the management of these disorders.